Medial Nasal Clusters in Indonesian - Lopez, Cecilio (The Archive, 2024)
Excerpt The existence of medial nasal clusters in PAN [Proto-Austronesian] (PIN [Proto-Indonesian] as the proto-language of the entire Austronesian family according to Dempwolff.) is admitted by many linguists. A few, however, do not share this view. The purpose of this paper is to assemble - from literature available to me - the views of those who admit such existence and those who do not, if only arouse the curiosity of those who may be interested to pursue the subject further. As far as I can ascertain, there is to date no comprehensive study on nasal clusters in IN [Indonesian]. A paper of this nature will have to lean heavily on Dempwolff’s three-volume VLAW [ Vergleichende Lautlehre des austronesischen Wortschatzes ]. An Appendix of 156 PAN forms from Dempwolff’s III AW with reflexes in the daughter languages is added for the benefit of others. The Philippine putative cognates are not verified. This study is limited to IN.